Protein nutrition and endurance exercise: What does science say? - Gibala, M. J.
Athletes, coaches and scientists have recognized for decades that training and nutrition are highly interrelated when it comes to improving performance. An accumulating body of scientific evidence now confirms that nutrition can profoundly influence the molecular and cellular processes that occur in muscle during exercise and recovery. This brief review analyzes the potential for performance enhancement through protein ingestion, whether during activity or by enhancing muscle recovery. Conclusions: Some studies have suggested that consuming protein with CHO during exercise improves endurance performance while other studies have reported no benefits. Additional research will resolve this debate, but it should be remembered that there is no established mechanism by which protein intake during exercise should improve performance. Recent evidence indicates that when CHO is consumed in sufficient amounts during exercise, adding protein provides no performance benefit and does not enhance muscle glycogen synthesis following exercise. Consuming a small amount (10-20 grams) of high-quality protein after exercise promotes muscle protein synthesis compared to CHO alone and may enhance the body`s response to long-term training.